Euro-Par 2010 - Parallel Processing 16th International Euro-Par Conference, Ischia, Italia, August 31 - September 3, 2010, Proceedings, Part I - DAmbra, Pasqua.; Guarracino, Mario.; Talia, Domenico. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 16th International Euro-Par Conference held in Ischia, Italy, in August/September 2010. The 90 revised full papers presented were carefully reviewed and selected from 256 submissions. The papers are organized in topical sections on support tools and environments; performance prediction and evaluation; scheduling and load-balancing; high performance architectures and compilers; parallel and distributed data management; grid, cluster and cloud computing; peer to peer computing; distributed systems and algorithms; parallel and distributed programming; parallel numerical algorithms; multicore and manycore programming; theory and algorithms for parallel computation; high performance networks; and mobile and ubiquitous computing.